Control versus execution: endogenous appropriability and entrepreneurial strategy. (24th September 2018) - Ching, Kenny; Gans, Joshua; Stern, Scott
Abstract: This article considers the role of Rosenbergian uncertainty (i.e., economic uncertainties that arise after successful invention) in shaping appropriability for start-up innovators. Rather than assuming that the appropriability regime surrounding an innovation is exogenous, we focus on the endogenous choice entrepreneurs face between investing in ensuring control-based appropriability versus investing in the execution and operation of their fledgling businesses. Investment in execution allows entrepreneurs to advance more quickly than competitors, while control requires delays in commercialization. Control and execution are strategic substitutes, as they represent alternative paths to earning future rents. Because the size and likelihood of these rents are uncertain, entrepreneurs may be unable to rank these alternative paths in advance, and so their endogenous choice will be grounded in factors such as individual preferences, capabilities, or coherence with their overall entrepreneurial strategy. A subtle consequence is that the appropriability regime ultimately governing an innovation will be the result of the endogenous choices of the entrepreneur rather than more traditional environmental factors. Motivated by notable historical examples such as the invention and commercialization of the telephone, we explore these ideas by considering the choice of appropriability regime among a sample of academic entrepreneurs: within a sample of ventures that could have been developed by either faculty or students (or both), we find that faculty-led ventures are much more closely associated with formal intellectual property, student-led ventures are more rapid in their commercialization activities, and, relative to faculty-led ventures, student-led ventures display a trade-off between patenting and commercialization speed.